The Impact of School and Parent Collaboration in Curriculum Implementation in Elementary School Education - Prihantini; Jimmi Hasmar (Jurnal Ilmiah Sekolah Dasar, 2024)
The education curriculum emphasizes the importance of parental involvement in children’s learning processes. Active parental participation is expected to enhance the effectiveness of education through collaboration between schools and parents. However, many schools face challenges in involving parents due to social disparities. This study aims to analyze parents' backgrounds and describe the results of school-parent collaboration in supporting children's education. The research utilized a quantitative method with a questionnaire as the primary instrument, developed based on indicators of parental involvement. The study involved 165 elementary school students and their parents as research subjects. Data were analyzed using SPSS through averaging each indicator and interpreting the results. The findings reveal a significant relationship between school-parent collaboration and children’s educational improvement. Parents’ involvement tends to increase when they feel their presence at school is appreciated by school authorities. Furthermore, parental participation is higher when schools collaborate with parents to discuss issues related to their children and provide information about meetings, activities, and programs that require parental attendance. In conclusion, effective school-parent collaboration positively impacts children's education by fostering a supportive learning environment and enhancing learning outcomes.